2022
DOI: 10.1186/s12886-022-02427-6
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric traumatic cataracts: 10-year experience of a tertiary referral center

Abstract: Background This study aimed to evaluate the factors influencing final visual acuity in pediatric traumatic cataracts. Methods Data of patients who presented with traumatic cataracts were reviewed retrospectively. We evaluated age at trauma; gender, trauma type, cause, and zone; duration between the time of trauma and cataract surgery; surgical method used; time, location, and type of intraocular lens (IOL) implantation; initial and final best corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…The severity of diminution of vision was also not much related to duration of trauma whether it was progressive or stationary. This finding was also similar to one study 11 in children with posttraumatic cataracts, where final visual acuity was not affected by patient age and gender; trauma type, cause, and zone; duration between the time of trauma and cataract surgery; surgical method used; and time, location, and type of intraocular lens (IOL) implantation and also similar to other studies. 10,12 Our study also shows that 40% of the cases show deviation in the range of 11 • -20 • (irrespective to divergence or convergence) and "Duration of trauma does not have any direct relationship with the amount of deviation because no case where duration was > 1 year" showed deviation more than 20 • while many patients where duration was less than 1 year, showed a deviation of > 20 • and this finding was also similar to other studies.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The severity of diminution of vision was also not much related to duration of trauma whether it was progressive or stationary. This finding was also similar to one study 11 in children with posttraumatic cataracts, where final visual acuity was not affected by patient age and gender; trauma type, cause, and zone; duration between the time of trauma and cataract surgery; surgical method used; and time, location, and type of intraocular lens (IOL) implantation and also similar to other studies. 10,12 Our study also shows that 40% of the cases show deviation in the range of 11 • -20 • (irrespective to divergence or convergence) and "Duration of trauma does not have any direct relationship with the amount of deviation because no case where duration was > 1 year" showed deviation more than 20 • while many patients where duration was less than 1 year, showed a deviation of > 20 • and this finding was also similar to other studies.…”
Section: Discussionsupporting
confidence: 90%
“…In our present study, about 3 4 of cases had progressive vision course just similar to studies. [6][7][8][9][10][11][12][13] Another interesting finding which came out from our study that about half of the cases of perforating injury showed signs of old anterior uveitis while this incidence was on 1/5 t h in cases of Blunt injury and about 1/3 of cases of traumatic cataract show signs of anterior uveitis. Our this finding was also similar to study 14 in Egypt where Twenty-one eyes sustained open globe injury (62%) with the most common cause of trauma was wooden sticks, while 13 eyes had closed globe injury (38%) with the most common cause of injury was thrown stones.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…On the other hand, visual acuity deterioration due to blunt trauma often occurs gradually, risking delayed proper treatment and undesirable prognosis in some children. 10 Posterior segment examination using an indirect ophthalmoscope should be performed to investigate abnormalities resulting from trauma. This can only be done if media clarity allows.…”
Section: Case Reportmentioning
confidence: 99%